1999
DOI: 10.1111/j.1530-0277.1999.tb04082.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Directly Excites Dopaminergic Ventral Tegmental Area Reward Neurons

Abstract: These data provide strong evidence that ethanol directly excites dopaminergic VTA neurons, as this excitation still occurs in the absence of input from surrounding neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
3
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 348 publications
(169 citation statements)
references
References 26 publications
9
156
3
1
Order By: Relevance
“…EtOH excitation in dopaminergic neurons of the rat has been shown to be blocked by quinidine, but not by blockers of h-current (Appel et al, 2003). Furthermore, EtOH excites individual VTA neurons dissociated from brain slices (Brodie et al, 1999;Ye et al, 2001), a preparation that would be expected to reduce the ability of synthesized ACD to act on these independent VTA neurons, and the concentration-response for EtOH excitation of dissociated dopaminergic VTA neurons (Brodie et al, 1999) is similar to that observed in brain slices (Brodie et al, 1990).…”
Section: Differences Between Acetaldehyde and Alcohol: Electrophysiolmentioning
confidence: 64%
“…EtOH excitation in dopaminergic neurons of the rat has been shown to be blocked by quinidine, but not by blockers of h-current (Appel et al, 2003). Furthermore, EtOH excites individual VTA neurons dissociated from brain slices (Brodie et al, 1999;Ye et al, 2001), a preparation that would be expected to reduce the ability of synthesized ACD to act on these independent VTA neurons, and the concentration-response for EtOH excitation of dissociated dopaminergic VTA neurons (Brodie et al, 1999) is similar to that observed in brain slices (Brodie et al, 1990).…”
Section: Differences Between Acetaldehyde and Alcohol: Electrophysiolmentioning
confidence: 64%
“…At the systems level, the increased release of DA associated with the administration of toluene and the CNS-depressant EtOH has been temporally associated in vivo with an increase in the number of impulses originating within the VTA, the site of origin of the mesolimbic DA pathway (Gessa et al, 1985;Riegel and French, 1999a, b). At the cellular level both substances stimulate DA neuronal activityFan effect that has been attributed to disinhibitory mechanisms as well as the direct activation of VTA DA neurons (Brodie et al, 1990(Brodie et al, , 1999. Taken together, these noticeable similarities would appear to support the general conclusions that the abused inhalant toluene may trigger the release of DA in the NAC via impulse-dependent mechanisms initiated upstream at the level of the cell bodies in the VTA.…”
Section: -Ohda Studies and Toluenementioning
confidence: 71%
“…In addition, the dopaminergic system has also been strongly implicated in alcohol abuse, particularly in mediating its acute reinforcing properties. Acute alcohol exposure can enhance the firing rate of dopaminergic cells in both the ventral tegmental area (VTA) (Brodie et al, 1999) and the substantia nigra (Mereu et al, 1984). This is thought to correspond to an increase in dopamine release in a number of brain regions, including the nucleus accumbens (Melendez et al, 2002;Gonzales et al, 2004), striatum (Melendez et al, 2003), the central nucleus of the amygdala (Yoshimoto et al, 2000) and the bed nucleus of the stria terminalis (BNST) (Carboni et al, 2000).…”
Section: Introductionmentioning
confidence: 99%